Database systems design, implementation, and management - Coronel, Carlos; Morris, Steven (Cengage, 2023)
Database skills are among the most in-demand IT skills. With its practical, accessible approach, Coronel/Morris' market-leading Database systems: design, implementation, and management, 14th edition, equips you with a solid foundation in database design and implementation for today's market. The authors blend foundational theory, the latest real-world practices and the skills employers want. Straightforward writing and vivid illustrations make even complex concepts easy to understand. You'll learn the key to successful database implementation as you study how to properly design databases that fit within the larger strategic data environment. Expanded coverage includes big data analytics, NoSQL and data visualization technologies. In addition, the MindTap digital platform gives you real-world, hands-on practice to help you prepare for a successful career in database design and management.